A study on the surface shape and roughness of aluminum alloy for heat exchanger using ball end milling. Issue 1 (September 2015) - Lee, E; Kim, Y; jeong, H; Chung, H
Abstract: Aluminum alloy is a material with a high strength-weight ratio and excellent thermal conductivity. It neither readily corrodes nor quickly weakens at low temperatures, but can be easily recycled. Because of these features, aluminum heat exchangers are widely used in aluminum alloy. In addition, the aluminum alloy used in other areas is expected to gradually increase. As a result, researchers have been continuously studying the cutting patterns of aluminium alloy. However, such studies are fewer than those on the cutting patterns of ordinary steel. Moreover, the research on ball end milling with aluminium alloys has not received much attention. Therefore, in this study, an attempt was made to find the optimal cutting pattern among the seven cutting patterns for the machining of the commonly used aluminum alloy using ball end milling for a heat exchanger. The optimal pattern was found by comparing the different shapes and surface roughness values produced by the seven patterns.